Development of a satellite method for Baltic ecosystem monitoring (DESAMBEM) - an ongoing project in Poland - Bogdan Wo¼niak; Adam Krê¿el; Jerzy Dera (Oceanologia, 2004)
A large national project: Development of a satellite method for Baltic ecosystem monitoring (DESAMBEM) for creating mathematical models and a complex algorithm for the remote sensing of the Baltic ecosystem and its primary production is described. The final aim of the project is the development of a routine remote sensing methodology for determining characteristics of the Baltic ecosystem such as distribution maps of surface temperature, water transparency, upwelling currents, phytoplankton blooms, radiation balance, pigment concentrations and primary production. The progress of the study and examples of results are presented.